Review of structural features and binding capacity of polyphenols to gluten proteins and peptides in vitro: Relevance to celiac disease - Ribeiro, Miguel (2020)
UIDB 50006/2020 UID/AGR/04033/2019 project-POCI-01-0145-FEDER-029068